Alliance formation propensity in a global industry network. (1st January 2011) - Contractor, Farok J.; Beldona, Sam; Kim, Changsu
What factors determine which firms in an industry ally with each other? This paper analyses a sample of 497 alliances, in ten countries, in the global pharmaceutical sector where alliances are prolific and central to corporate strategy. The results suggest that direct technological commonality (measured by cross patent citations between each pair), indirect commonality (measured by the degree to which they share common third-party technology sources), and prior alliance ties statistically explain the propensity that any two firms in a network will form an alliance. We also explore cross-border effects to see if companies originating in different nations are more likely, or less likely, to form alliances because of their national origins.